The Columbia guide to the Latin American novel since 1945 - Williams, Raymond L. (Columbia guides to literature since 1945., 2007)
In this expertly crafted, richly detailed guide, Raymond Leslie Williams explores the cultural, political, and historical events that have shaped the Latin American and Caribbean novel since the end of World War II. In addition to works originally composed in English, Williams covers novels written in Spanish, Portuguese, French, Dutch, and Haitian Creole, and traces the profound influence of modernization, revolution, and democratization on the writing of this era. Beginning in 1945, Williams introduces major trends by region, including the Caribbean and U.S. Latino novel, the M.